2017
DOI: 10.1136/bmjopen-2016-014661
|View full text |Cite
|
Sign up to set email alerts
|

Treatment targeted at underlying disease versus palliative care in terminally ill patients: a systematic review

Abstract: ObjectiveTo assess the efficacy of active treatment targeted at underlying disease (TTD)/potentially curative treatments versus palliative care (PC) in improving overall survival (OS) in terminally ill patients.DesignWe performed a systematic review and meta-analysis of randomised controlled trials (RCT). Methodological quality of included RCTs was assessed using the Cochrane risk of bias tool.Data sourcesMedline and Cochrane databases were searched, with no language restriction, from inception to 19 October 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Poor performance status patients (ECOG-PS ≥ 2) usually tolerate chemotherapy poorly, with increased toxicity compared to patients with ECOG-PS 0-1. 46,47 In the present study, poor performance status was also a predictor of toxicity in gastrointestinal cancer patients. This underscores the need to identify clinical characteristics of poor performance status patients, avoiding overtreatment.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Poor performance status patients (ECOG-PS ≥ 2) usually tolerate chemotherapy poorly, with increased toxicity compared to patients with ECOG-PS 0-1. 46,47 In the present study, poor performance status was also a predictor of toxicity in gastrointestinal cancer patients. This underscores the need to identify clinical characteristics of poor performance status patients, avoiding overtreatment.…”
Section: Discussionsupporting
confidence: 53%
“…The present univariate model only suggested a maintained association between cachexia and ECOG with toxicities when the model was adjusted in multivariable analyses. Poor performance status patients (ECOG‐PS ≥ 2) usually tolerate chemotherapy poorly, with increased toxicity compared to patients with ECOG‐PS 0–1 . In the present study, poor performance status was also a predictor of toxicity in gastrointestinal cancer patients.…”
Section: Discussionsupporting
confidence: 49%
“…A systematic review on terminally ill cancer patients showed that active, potentially curative treatments had less efficacy in improving overall survival and increased toxicity, as compared with palliative care approaches. 39 Prognosis of ESC patients who received chemotherapy was not improved, 40 and they were more likely to die in intensive care units rather than in their own homes. 41 Considering physician and patient's awareness to the adverse events of chemotherapy, it is surprising that almost a quarter of our terminally ill patients were still receiving oncological therapies 2 weeks before death.…”
Section: Who Is Responsible To De-prescribe In End-stage Cancer Patmentioning
confidence: 99%
“…[4][5][6] Realistic estimates of overall survival are particularly important for patients with a diagnosis of cancer who need to make decisions about the risks and benefits of active versus supportive treatment (eg, whether to have surgery, chemotherapy, radiotherapy, or palliative care). 7 Current evidence suggests that issues around survival are only discussed properly in approximately 30% of cases. 8 This may reflect a lack of robust information on survival, which takes account of patient characteristics and the likely effect of different treatments.…”
Section: Introductionmentioning
confidence: 99%